Comprehensive textbook of perioperative transesophageal echocardiography - Savage, Robert M., 1950-; Aronson, Solomon.; Shernan, Stanton K.; Shaw, Andrew. (Wolters Kluwer/Lippincott Williams & Wilkins Health, 2011)
"Upon publication, the Savage/Aronson text immediately became the definitive TEE reference. The Second Edition has been significantly reorganized to meet new demands in the market. The first section covers material relevant to the basic certification now being implemented by the American Society of Anesthesiologists and the Society of Cardiovascular Anesthesiologists. The second section, new to this edition, covers echocardiography in the critical care setting. The third section covers advanced applications relevant to the current certification. The basic perioperative echocardiography section includes new chapters on organizing education and training in perioperative echocardiography and on ultrasound for vascular access. The critical care section includes new chapters on assessment of the patient with endocarditis and using echo during resuscitation. The advanced applications in perioperative echocardiography section includes new chapters on epiaortic and epicardial imaging; endovascular management of thoracic vascular disease; transcutaneous management of valvular heart disease; and perioperative application of Strain and three-dimensional echocardiography. A companion website includes the fully searchable text and an image bank"--Provided by publisher.